Didactic discussions during ESL/EFL English teacher training courses. Issue 1 (2nd January 2021) - Carabelli, Patricia
ABSTRACT: During teacher training courses, pre-service teachers acquire not only aspects regarding specific content they must teach, in this case English as a Second and Foreign Language, they also analyse different pedagogical approaches and reflect on their practical implementations. At present, student-centred approaches are being implemented in educational systems and they demand complex perspectives focused on interaction and reflective practices. One way of promoting these approaches is by incorporating didactic discussions based on the meta-analysis of recorded lessons that are presented as case studies. By watching and examining specially chosen video-recorded lessons, prospective teachers reflect upon and discuss different teaching and learning approaches, classroom management strategies, ways of interacting, and classroom arrangements. A mixed research approach, based on interviews and a classroom survey, was carried out during two consecutive years in an English teacher training programme in Uruguay to evaluate the effectiveness of didactic discussions based on the observation of video-recorded lessons. All of the pre-service teachers stated that the discussions and debates the video-recorded lessons triggered, helped them understand and acquire important pedagogical notions that helped them teach in more confident and effective ways.